การประยุกต์ใช้หลักปรัชญาเศรษฐกิจพอเพียงเพื่อส่งเสริมการเรียนรู้ในศตวรรษที่ 21 - โพดาพล, จักรกฤษณ์ (วารสารศรีล้านช้างปริทรรศน์, 2017)
การเรียนรู้ในศตวรรษที่ 21 นักเรียนต้องมีความอยากรู้ สงสัยใคร่รู้เอง ครูคอยกระตุ้นให้เกิดความใคร่รู้ นักเรียนลงมือศึกษาเอง โดยอาศัยความวิริยะ ครูเป็นเพียงผู้ชี้แนะ ให้คำปรึกษา เพื่อให้นักเรียนจดจ่อในการเรียนรู้อย่างมีสมาธิ และคอยคิดวิเคราะห์ใคร่ครวญความรู้นั้น ให้ต่อยอดออกไปเรื่อย ๆ การนำเอาหลักปรัชญาเศรษฐกิจพอเพียงของพระบาทสมเด็จพระปรมินทรมหาภูมิพลอดุลยเดช มาประยุกต์ใช้ในการส่งเสริมการเรียนรู้ของนักเรียน นักศึกษา เป็นการนำเอาองค์ประกอบส่วนที่เป็น 3 ห่วงซึ่งประกอบด้วย พอประมาณ มีเหตุผล และมีภูมิคุ้มกันที่ดีในตัวเอง ได้มาประยุกต์เป็นแนวทางปฏิบัติ ดังต่อไปนี้           พอประมาณ เป็นการคะเนให้ใกล้เคียงจำนวนจริงหรือให้พอเหมาะพอควร ใช้การวิเคราะห์ตนเอง โดยการทำการวิเคราะห์สวอต (SWOT Analysis) ความมีเหตุผล คือการวางแผนอนาคตทั้งการกำหนดเป้าหมายระยะยาวหรือวิสัยทัศน์ การกำหนดเป้าหมายระยะสั้น และการกำหนดแนวทางการดำเนินชีวิต โดยคำนึงถึงความเป็นไปได้จากการวิเคราะห์ตนเอง การเป็นตัดสินใจเกี่ยวกับระดับของความพอเพียงนั่นเอง ภูมิคุ้มกันที่ดีที่จะสามารถคุ้มกันชีวิตนักเรียน นักศึกษาก็คือ การมีวินัยในตนเอง ป้องกันจากภัยคุกคามที่สำคัญคือ การเรียนไม่จบ และไม่สามารถเดินตามเส้นทางไปอยู่ในภาพที่ตัวเองฝันเอาไว้ได้ สาเหตุเกิดจากสภาพแวดล้อมในปัจจุบัน           In the 21 st Century Learning, the learner is much curious while the teacher plays an important role to encourage him eager to know and the learner makes an effort study by himself without any assistance. The teacher is only a director to give any suggestion which will make the learner suspensive and concentrated at learning until he can critically think over knowledge and further extend the knowledge. The application of His Majesty King Bhumibol Adulyadej's philosophy of sufficiency economy to support the learning of students is regarded as the combination of three substituents: moderation, prudence and social immunity as the practical guideline in living as follows:           The word ‘moderation’ means the expectation and the estimate of the real or appropriate amount based on self-analysis by means of the SWOT Analysis. The word ‘prudence’ means the planning for the future, including the setting of the long-term goal or the vision, the setting of the short-term goal and the setting of the way of life under the feasibility of self-analysis, which means the decision on the level of sufficiency. Good social immunity, able to protect the student’s living life, is self-discipline to prevent him/her from an important threat of ungraduatedness and inability to reach the destination, which he/she imagines, as a result of the current situation.